Functional state of the diaphragm in patients with chronic obstructive pulmonary disease on long-term oxygen therapy - O. N. Titova (Bûlleten' Sibirskoj Mediciny, 2017)
Purpose. To study the functional state of the diaphragm in patients with chronic obstructive pulmonary disease (COPD) complicated by chronic hypoxemia.Materials and methods. The study included 90 patients with COPD III–IV stages, group D (GOLD, 2015): 45 patients with chronic hypoxemia and 45 normoxemic patients. The following parameters were analyzed: spirometric level, oxygen saturation and arterial blood oxygen, breathlessness (by the Modified British Medical Research Council Questionnaire), rate of COPD exacerbations. Ultrasound examination of the diaphragm was conducted.Investigations were carried out twice: at baseline and after 12 months of observation. All patients with chronic hypoxemia were prescribed long-term oxygen therapy (LTOT).Results. The study of functional indicators in COPD patients revealed that the presence of hypoxemia was characterized, as compared with normoxemic patients, not only by more severe breathlessness and airflow limitation, but the alteration of diaphragmatic function. LTOT appointment in hypoxemic patients was accompanied in a year by changes in the functional state of the diaphragm (increase in relaxation rate of the diaphragm during quiet breathing) and a reduction in the number of COPD exacerbations.Conclusion. The shift in diaphragm function could mediate the positive impact of LTOT on COPD prognosis, including the number of COPD exacerbations in patients with hypoxemia.